(untitled) (Bioscience Journal, 2023)
This intervention follow-up study evaluated anxiety and stress levels and self-perceived happiness of individuals linked to the health field who did not practice Tai Chi and compared these variables before and after practicing this art. One hundred twenty-three participants were subdivided into two groups: G1) Older health professionals (n=41) and G2) Younger pre-university students interested in the health field (n=82). Participants received a 60-minute Tai Chi class. The Perceived Stress Scale (PSS-14) was applied before the practice, and the State-Trait Anxiety Inventory (STAI) and Andrews Face Scale were used before and after the class. Generalized linear models and the Bowker symmetry test were applied for data analysis. 46.3% and 30.5% of participants in G1 and G2 had mild stress levels, and 43.9% and 46.3% had moderate stress levels, respectively. After practicing Tai Chi, both groups presented significantly lower mean anxiety scores. In G1, 31.7% of participants went from moderate to mild anxiety levels after practice, 19.5% from severe to moderate, and 7.3% from severe to mild. In G2, 28.2% of participants went from moderate to mild anxiety levels after practice, 18.3% from severe to moderate, and 6.1% from severe to mild. Furthermore, 100.0% of individuals in G1 and 96.3% in G2 were happy after the class. Tai Chi was effective in reducing anxiety levels and improving self-perceived happiness.